Considerations on the Institutional Independence Statute of the Romanian Court of Accounts - Elena–Carmen BRAGADIREANU (Revista de Management Comparat International)
The article is an analysis of the way the principle of independence works at the level of the Romanian Court of Accounts, the institution habilitated by legal provisions to conduct the financial control/audit activity, in order to obtain an assurance that the financial resources required to cover common needs, their distribution in relation to the priorities set by the competent bodies, as well as the use of public funds are unfold in conditions of economical and social efficiency, involving harmonization of interests, sizing of financial resources and, last but not least, their channeling towards various programmed destinations.